Effect of the trout aquacultural activity on the number of total coliforms and Escherichia coli in the upper drainage basin of the Savegre river, Costa Rica - Retana L., Marco (2023)
Introduction: Development of trout aquacultural activity has gradually increased in Costa Rican highlands. Residual waters from this activity are discarded directly on the rivers without any previous treatment process. Consequently, this activity could severely contaminate the river with bacteria that can affect the human health. Objective: The objective of this study is to evaluate the bacteria contamination caused by the residual water from the trout aquacultural activity discarded directly on the upper drainage basin of the Río Savegre. Methods: We counted the number of total coliforms and Escherichia coli from samples obtained monthly (2015-2018) at 3 sections of the largest aquacultural development in the upper drainage of the river. We collected samples at the entrance of the fish ponds, at the exit, and 200 m downwards. We compared the bacteria counts among locations and sampling years. Results: We found fewer total coliforms and E. coli in the water collected just at the exit of the fish ponds. We counted more total coliforms in 2016 and 2017, and more E. coli in 2016. Conclusions: The number of total coliforms and E. coli is very high in the river, but unexpectedly their number decreased in the water discarded from the fish tanks. The contamination of the river is likely caused by the water produced by other human activities and other aquaculture developments that discard the residual water directly on the river. We speculate the mucus produced by the trouts or substances released by the moss that cover the wall of fish tanks could regulate the growth of bacteria populations as has been suggested in other studies. Objective: The objective of this study is to evaluate the bacteria contamination caused by the residual water from the trout aquacultural activity discarded directly on the upper drainage basin of the Río Savegre. Methods: We counted the number of total coliforms and Escherichia coli from samples obtained monthly (2015-2018) at 3 sections of the largest aquacultural development in the upper drainage of the river. We collected samples at the entrance of the fish ponds, at the exit, and 200 m downwards. We compared the bacteria counts among locations and sampling years. Results: We found fewer total coliforms and E. coli in the water collected just at the exit of the fish ponds. We counted more total coliforms in 2016 and 2017, and more E. coli in 2016. Conclusions: The number of total coliforms and E. coli is very high in the river, but unexpectedly their number decreased in the water discarded from the fish tanks. The contamination of the river is likely caused by the water produced by other human activities and other aquaculture developments that discard the residual water directly on the river. We speculate the mucus produced by the trouts or substances released by the moss that cover the wall of fish tanks could regulate the growth of bacteria populations as has been suggested in other studies.